AB0606 Systemic Sclerosis and Recurrent Pregnancy Loss: Possible Role of Autoantibody Profile and Microvascular Damage. (10th June 2014) - Corrado, A.; Neve, A.; Marucci, A.; Colia, R.; Di Bello, V.; Cantatore, F.P.
Abstract : Background: Systemic sclerosis (SSc) is an autoimmune connective tissue disease characterized by fibrosis, autoimmunity and widespread microangiopathy. Vascular damage is a hallmark of SSc and plays a key role in the pathogenesis of some of the most characteristic clinical manifestations, including digital ulcers, pulmonary arterial hypertension and scleroderma renal crisis. An increased risk of pregnancy complications, particularly pregnancy loss, has been reported in patients with SSc, but less is known about the pathogenic mechanisms involved in this event and the potential role played by microvascular damage and autoimmunity is still unclear. Objectives: The aim of this study is to evaluate the prevalence of recurrent pregnancy loss in SSc patients and to investigate the possible relationship with organ involvement, autoantibody profile and capillaroscopic abnormalities. Methods: We retrospectively analyzed data from 68 SSc patients, fulfilling the 2013 EULAR/ACR diagnostic criteria. In addition to basic demographic features, for each recruited patient we analyzed the disease characteristic, including the extent of skin fibrosis, the pattern of internal organ involvement and the prevalence of digital ulcers (DU). Patients were classified in 3 groups according to autoantibody profile (anti Scl70+, ACA+, Ab-). We evaluated the prevalence of recurrent pregnancy loss, defined as ≥2 fetal loss, and the presence of anti cardiolipin antibodies (aCL), anti β2GPI antibodies and LAC in the clinical history of recruited patients. Microangiopathy was assessed by nailfold videocapillaroscopy and capillary abnormalities were scored as "Early", `Active" and "Late" pattern. Results: No difference in prevalence of recurrent fetal loss was observed between patients anti Scl70 + and ACA+, whereas in patients Ab- the prevalence of recurrent fetal loss was significantly lower (p<0, 01). Among subjects with previous history of recurrent fetal loss, aCL, anti β2GPI and/or LAC were positive in all patients Ab-, whereas they were detected only in a small percentage of patients anti Scl70+ (25%) and ACA+ (15, 38%). Concerning microagiopathy, all patients Ab- showed an "Early" capillaroscopic pattern, whereas the "Active" and "Late" patterns were the prevalent capillaroscopic abnormalities observed in patients anti Scl70+ (44, 5% "Active", 22, 2% "Late") and ACA+ (46, 2% "Active", 15, 3% "Late"). None of Ab- patients presented a clinical a history of DU, which were observed in anti Scl70+ (44, 5%) and ACA+ (30, 7%) patients. No differences were observed concerning internal organ involvement (heart, gastrointestinal, musculo-skeletal, kidney) and disease duration between anti Scl70+, ACA+ and Ab- groups, excepted for interstitial lung disease that was significantly more frequent in anti Scl70+ patients (p<0, 05). Conclusions: These preliminary data suggest that microvascular damage could be related with recurrent pregnancy loss in SSc, especially in anti SCL70+ and ACA+ patients. The role of antiphospholipid syndrome could play a preminent role only in a subgroup of patients, with a particular autoantibody profile (Ab-), which present a less severe microvacular involvement. References: Miniati I et al. J Rheumatol 2008;47:16-18 Lidar M et al. Autoimm Rev 2012;11:A515-9 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2389